Biomimetics 2013
DOI: 10.1002/9781118810408.ch1
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Polysaccharides and Derivatives for Cartilage Tissue Regeneration

Abstract: Cartilage tissue engineering is an emerging technology for the regeneration of such tissues damaged by disease or trauma. Unlike other types of tissue, cartilage does not have a blood supply and, therefore, lacks regenerative capabilities. Hence, there is an urgent need to develop cartilage tissues in clinically translatable conditions for regeneration. This fi eld of research involves the choice of the appropriate cells and biomaterials, devising signaling factors to the defect site for regeneration. The obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 115 publications
(119 reference statements)
0
4
0
Order By: Relevance
“…HA is the Food and Drug Administration (FDA) approved biomaterial for human application, and clinical trials confirmed that HAs are effective for osteoarthritis applications [ 30 , 31 , 32 ]. Chitosan ( Figure 1 c) is an important class of polysaccharide consisting of multiple functional groups, allowing ease of chemical modification, and has been used as a delivery agent, as well as in cell encapsulation, cellular functioning, and differentiation toward TE application [ 5 , 16 , 33 , 34 ]. Alginate is another example of a polysaccharide that has been used for cell encapsulation and injectable gel in TE [ 35 ].…”
Section: Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…HA is the Food and Drug Administration (FDA) approved biomaterial for human application, and clinical trials confirmed that HAs are effective for osteoarthritis applications [ 30 , 31 , 32 ]. Chitosan ( Figure 1 c) is an important class of polysaccharide consisting of multiple functional groups, allowing ease of chemical modification, and has been used as a delivery agent, as well as in cell encapsulation, cellular functioning, and differentiation toward TE application [ 5 , 16 , 33 , 34 ]. Alginate is another example of a polysaccharide that has been used for cell encapsulation and injectable gel in TE [ 35 ].…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…To date, most synthetic biomaterials are derived for TE application, which are synthesized either from lactic acid, caprolactone, or glycolide monomers to form poly( l -Lactide), or poly(ε-caprolactone), or poly( l -glycolic acid), respectively, and/or their combination to form copolymers, or the physical blending of these polymers [ 11 , 12 ]. Natural polymers such as chitosan, alginate, starch, collagen, hyalauronic acid, cellulose, fibrin, silk, and their derivatives are also used [ 5 , 15 , 16 ]. A variety of techniques and methods has been developed to fabricate biomaterial scaffolds to control shapes, sizes, porosities, and architectures for TE applications [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan, alginate, starch, collagen, HA, cellulose, fibrin, silk, and their derivatives may also be utilized to build scaffolds [ 20 ]. To manage the lengths, thicknesses, porosities, and structures of biomaterial-related scaffolds for TE applications, a range of approaches and techniques have been explored [ 21 ].…”
Section: Biomaterials For Tissue Regenerationmentioning
confidence: 99%
“…There is also no concern of immunogenicity or the presence of pathogenic agents. Nondegradable polymers such as ultra-high molecular weight polyethylene have been used in the production of acetabular cups used in total hip arthroplasty [17]. Over the past decade, degradable polymer bone substitutes have been used more and more since it is ideal to have a synthetic graft that is completely resorbed leaving no foreign material behind.…”
Section: Polymer Basedmentioning
confidence: 99%